Megakaryocytes in the Giant Platelet Syndrome - Kass, Lawrence; Leichtman, David A.; Beals, Theodore F.; Schnitzer, Bertram (Thrombosis and Haemostasis, 1977)
When compared to normal megakaryocytes, those from a patient with the giant platelet syndrome exhibited numerous cytochemical abnormalities. These reflected disturbances in the metabolism of RNA, glycogen, arginine-rich histone, and various glycolytic enzymes. Ultrastructural studies of the abnormal megakaryocytes also showed decreased glycogen and RNA (ribosomes) as well as aberrations of nuclear lobulation.